Essays in self-portraiture a comparison of technique in the self-portraits of Montaigne and Rembrandt - Small, Andrew (Lang, 1996)
By pairing specific self-portraits, the author compares Rembrandt and Montaigne in terms of courtiership and in terms of religious wisdom and ignorance. The book closes by showing how both artists used dissimilarity in their self-portraits. By selectively embracing and rejecting certain exemplars, Montaigne and Rembrandt constructed two of our most complete examples of the early modern self
Keywords: Montaigne, Michel de <1533-1592> - Autoportraits; Rembrandt <1606-1669> - Autoportraits; Montaigne, Michel de <1533-1592> -- Technique; Rembrandt Harmenszoon van Rijn <1606-1669> -- Self-portraits; Rembrandt -- Harmensz van Rijn -- 1606-1669; Montaigne, Michel Eyquem de -- 1533-1592; Autoportraits - Aspect psychologique; Psychologie; Arts, Modern; Self in literature; Self-portraits -- Psychological aspects; Selbstdarstellung; Selbstbildnis; Selbstbild